That’s not funny! – But it should be: effects of humorous emotion regulation on emotional experience and memory - Kugler, Lisa; Kuhbandner, Christof (Frontiers in Psychology, 2015)
Previous research has shown that humorous reappraisal can reduce elicited negative emotions, suggesting that humor may be a functional strategy to cope with emotionally negative situations. However, the effect of humorous reappraisal on later memory about the emotion-eliciting situation is currently unknown, although this is crucial for more adaptive responding in future situations. To address this issue, we examined the effects of humorous reappraisal on both emotional experience and memory, compared to non-humorous rational reappraisal and a non-reappraisal control condition. Replicating previous findings, humorous reappraisal reduced evoked negative valence and arousal levels very effectively, and the down-regulation of experienced negative emotions was even more pronounced after humorous compared to rational reappraisal. Regarding later memory for emotion-eliciting stimuli, both humorous and rational reappraisal reduced free recall, but recognition memory was unaffected, with memory strength being stronger after humorous than after rational reappraisal. These results indicate that humor seems to be indeed an optimal strategy to cope with negative situations because humor can help us to feel better when confronted with negative stimuli, but still allows us to retrieve stimulus information later when afforded to do so by the presence of appropriate contextual features.